Alanine dehydrogenase and its applications – A review. (4th July 2019) - Dave, Ushmaben Chandrakantbhai; Kadeppagari, Ravi-Kumar
Abstract: Alanine dehydrogenase (AlaDH) (E.C.1.4.1.1) is a microbial enzyme that catalyzes a reversible conversion of L-alanine to pyruvate. Inter-conversion of alanine and pyruvate by AlaDH is central to metabolism in microorganisms. Its oxidative deamination reaction produces pyruvate which plays a pivotal role in the generation of energy through the tricarboxylic acid cycle for sporulation in the microorganisms. Its reductive amination reaction provides a route for the incorporation of ammonia and produces L-alanine which is required for synthesis of the peptidoglycan layer, proteins, and other amino acids. Also, AlaDH helps in redox balancing as its deamination/amination reaction is linked to the reduction/oxidation of NAD + /NADH in microorganisms. AlaDH from a few microorganisms can also reduce glyoxylate into glycine (aminoacetate) in a nonreversible reaction. Both its oxidative and reductive reactions exhibit remarkable applications in the pharmaceutical, environmental, and food industries. The literature addressing the characteristics and applications of AlaDH from a wide range of microorganisms is summarized in the current review.